Revisioning playground design for the developing world school campus: a nature playground proposal for La Chuscada, Nicaragua - Jarrett, Glen (Kansas State University, 2015)
Play is essential to the development of children, as it serves as the main platform for a child to begin to explore his or her world and understand their physical and social environment. It is not a frivolous activity, but a method of learning. Despite this recognition, many playground designs are still steered, wrongly so, by unwarranted societal fears of safety. Such playgrounds lack developmental benefits due to their composition of isolated, prefab plastic components on an asphalt field. Despite recognition in the late twentieth century that “childhood itself is in danger of extinction”, many playground are still sterile in nature. The time is now for designers to look critically at playground design trends and intervene to improve the quality of the environments our children are exposed too. The positive development of the next generation, our children, depends on it. In the case of the community of La Chuscada in Chinandega, Nicaragua, economic status presents a major barrier to the creation of beneficial learning environments. This project addresses the hardships of implementing a developmentally beneficial playground, and through the collaboration with the Amigos for Christ philanthropic organization and interior architecture student Aaron Bisch, offers solutions to achieve this goal. Culture-specific influences of play are explored and survey data from the community of La Chuscada reveal strategies for the implementation of a nature playground design that offers developmental benefits for the children of the community.
Keywords: Playground design; Nature play; Community engagement; Nicaragua; Child development; Early Childhood Education (0518); Landscape Architecture (0390)